(untitled) (Research, Society and Development, 2021)
Objective: The article aims to present the advantages of palliative care (PC) for patients with chronic kidney disease (CKD) and highlight the knowledge needed by nephrologists to offer holistic and appropriate treatment to these patients. Methods: This review was produced using Pubmed (American National Library of Medicine), the Virtual Health Library (VHL) and the Scientific Eletronic Library Online (SciELO). The advanced search had as descriptors: palliative care, chronic kidney disease and advance care planning. Subsequently, articles in English and Portuguese with publications between 2015 and 2020 were filtered, with the most relevant being selected. Results: The analysis of the references elucidated the PC and its role in CKD, the skills inherent to nephrologists and the main symptoms of patients with CKD. Conclusion: The early introduction of palliative care is necessary to improve the quality of life of patients with CKD, without restricting it to end-of-life measures and without excluding interventionist procedures. Thus, it is essential to invest in the training of nephrologists to meet the demands of palliative care in CKD.